A STUDY ON’ VOCABULARY MASTERY OF THE THIRD YEAR STUDENTS’ OF THE STATE JUNIOR HIGH SCHOOL (SMPN) 40 PEKANBARU IN NARRATIVE TEXTS - Saffana Tuzzakiroh; Supriusman Supriusman; M. Syarfi M. Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The purpose of this quantitative research was to find out the vocabulary mastery of the third year students of SMPN 40 Pekanbaru. The study sample was 35 students. The result of data analysis showed that multiple-choice test 1 was 37.6 and categorized into “very poor level” and test 2 was 57.8 and categorized into “average level”. The conclusion concerning the category classification is “very poor to average “which mean that vocabulary mastery of the third year students of SMPN 40 Pekanbaru was categorized into “low average level” for achievement in English lesson. The writer suggests that teachers are recommended to improve students' vocabulary by presenting interesting materials, and then give them homework, and exercises at school.Key Words: Vocabulary, Mastery, Narrative Text